Effects of physical, psychosocial and dual-career loads on injuries and illnesses among elite handball players: protocol of prospective cohort study. Issue 3 (2nd March 2023) - Drole, Kristina; Paravlic, Armin; Steffen, Kathrin; Doupona, Mojca
Abstract : Introduction: Health problems in sport cause a major burden on several pillars: sport clubs, health and insurance system and mostly the individual athlete. There is limited knowledge in supporting dual-career athletes firmed on evidence-based research in injury/illness prevention, load and stress management. The main goal of this research approach is to determine how specific physical, psychosocial and dual-career loads affect the occurrence of injuries and illnesses in elite handball players and how much of a variation in the athlete's load leads to an occurrence of an injury/illness. A secondary aim is to determine the association between objective and subjective measures of stress as well as examine the benefits of certain biomarkers to monitor stress, load and injury/illness occurrence in athletes. Methods and analysis: This prospective cohort study, as part of a PhD project, will be carried out on 200 elite handball players of first men's handball league in Slovenia during an entire handball season, lasting from July 2022 to June 2023. Primary outcomes, including health problems, loads and stress, will be assessed weekly on a player level. Other player-related outcomes will include anthropometry, life event survey and blood biomarkers (cortisol, free testosterone and Ig-A), which will be taken three to five times across the observation period according to the players' training cycle. Ethics and dissemination: The project was approved by the National Medical Ethics Committee of Slovenia (number: 0120-109/2022/3) and will be conducted in compliance with the most recent version of Helsinki Declaration. The study results will be published as peer-reviewed articles, congress presentations and as a Doctoral thesis. The results will not only be of importance for the medical and sports community for development of new injury prevention and rehabilitation strategies but also for structuring the correct policy recommendations for athletes' general health. Trial registration number: NCT0547129 .